Perspectives of cruise tourism in the City of Rijeka - Jugović, Alen (2020)
This article discusses a type of activity, level of consumption, and cruise ship tourists’ satisfaction in a destination to understand the perspectives of cruise tourism in the city. Design/Methodology – The research was conducted during 2018 by personal interviews or website questionnaires among 163 cruise tourists in the city of Rijeka, Croatia. The survey included 15 questions that were categorized into five thematic units. The data were processed by descriptive statistics. Findings – According to a slight increase in travelers’ consumption but also their overall satisfaction, the results suggest an increase in destination attractiveness. The economic results are still at a modest level. A set of measures has been proposed to improve tourism services in the destination. Originality of the research – Given those cruise companies are permanently on the lookout for attractive destinations, it is up to cities to attract cruise ships to their ports. It is necessary to assess and check the tourists’ experience of a cruise destination permanently so that the offerings of port city can be adjusted to the changing demands of passengers. Limiting factors associated with cruising point to caution in assessing the future of cruise tourism, especially in a city where this kind of business is just beginning.
Bibliografija: 39 jed.
Abstract.
Keywords: Krstarenje -- Potrošnja -- Zadovoljstvo -- Turističko odredište; Rijeka